The Optimatization of Kissing Gourami (Helostoma temminckii) Fry Density in Recirculation System Culture - M Tansuka; Ferdinand H Taqwa; Retno C Mukti (Jurnal Lahan Suboptimal : Journal of Suboptimal Lands, 2022)
Kissing gourami (Helostoma temminckii) is a type of swamp fish that has the potential to be cultivated. The increasing of yield for this fish can be done by optimization of stocking density. The problem of aquaculture with high stocking density is decreased water quality, growth and fish survival. One of the efforts to overcome this problem is through the management of the cultivation environment using a recirculation system. The purpose of this study was to determine the optimal density of kissing gourami fry on a recirculation system. This research method used a completely randomized design (CRD) using 4 treatments of fish stocking density (2, 3, 4, and 5 fish/L, respectively),  which was carried out with 3 replications. The parameters observed included water quality, growth, survival rate, and fish blood glucose level. The results of this study indicated that the best density was 2 fish/L with absolute weight growth was  0.55 ± 0.03 g, absolute length growth was 0.53 ± 0.05 cm, survival rate was 86.67 %, blood glucose levels were 50.67−52.56 mg/dL and food conversion ratio was 1.29. The water quality value during the fish rearing was in the appropriate range, i.e. temperature 28.4−30.4°C, pH 6.6−7.4, dissolved oxygen 5.08−6.54 mg/L and ammonia 0.12−0.25 mg/L.